MODEL PARKIR BERBASIS AUTOMATIC PARKING SYSTEM PADA KAWASAN PARIWISATA (STUDI KASUS DI DESTINASI WISATA KUTA, BALI) - I Gusti Ayu Eka Suwintari; I Made Trisna Semara; I Nyoman Sudiarta (Jurnal Ilmiah Hospitality Management, 2019)
In the tourism area the vehicle population continues to increase, on the other hand the lack of public facilities that are safe and comfortable as a medium of transportation causes most tourists to prefer carrying private vehicles. Meanwhile tourist attractions in tourist areas are usually centered on a particular location. This will also result in high concentration of vehicles in the area. Then the availability of parking lots is needed. The problem is the need for land for other purposes is also increasing and the availability of vacant land is also limited. Resulting in several problems such as parking on the roadside which will then hamper vehicle circulation activities. The research objective is to identify parking system problems in the Kuta tourism area and create ideas in the direction of the development of parking infrastructure referring to the development of multi-storey parking buildings (Vertical) with the application of the parking system system with APS (Automatic Parking System) technology. This research is a research with a qualitative descriptive analysis approach which is done by data collection techniques through direct observation, document studies, and literature studies.